The Bimodal Lifestyle of Intracellular Salmonella in Epithelial Cells: Replication in the Cytosol Obscures Defects in Vacuolar Replication - Malik-Kale, Preeti; Winfree, Seth; Steele-Mortimer, Olivia (PLOS ONE, 2012)
Salmonella enterica serovar Typhimurium invades and proliferates within epithelial cells. Intracellular bacteria replicate within a membrane bound vacuole known as the Salmonella containing vacuole. However, this bacterium can also replicate efficiently in the cytosol of epithelial cells and net intracellular growth is a product of both vacuolar and cytosolic replication. Here we have used semi-quantitative single-cell analyses to investigate the contribution of each of these replicative niches to intracellular proliferation in cultured epithelial cells. We show that cytosolic replication can account for the majority of net replication even though it occurs in less than 20% of infected cells. Consequently, assays for net growth in a population of infected cells, for example by recovery of colony forming units, are not good indicators of vacuolar proliferation. We also show that the Salmonella Type III Secretion System 2, which is required for SCV biogenesis, is not required for cytosolic replication. Altogether this study illustrates the value of single cell analyses when studying intracellular pathogens.